Weight-loss interventions for overweight/obese adults with chronic musculoskeletal pain: a mixed methods systematic review protocol. (May 2016) - Cooper, Lesley; Ryan, Cormac; Ells, Louisa Jane; Hamilton, Sharon; Atkinson, Greg; Cooper, Kay; Johnson, Mark I.; Kirwan, John P.; Martin, Denis
Abstract : Review question/objective: The objective of this mixed methods review is to develop an aggregated synthesis of qualitative and quantitative data on weight-loss interventions for overweight/obese adults with chronic musculoskeletal pain in an attempt to derive conclusions and recommendations useful for clinical practice and policy decision making. The objective of the quantitative component of this review is to quantify the effectiveness of weight-loss interventions on weight, pain and physical and/or psychosocial function in overweight/obese adults with chronic musculoskeletal pain. The objectives of the qualitative component of this review are to explore the perceptions and experiences of overweight/obese adults with chronic musculoskeletal pain of the link between their weight and pain, and the effectiveness and appropriateness of weight-loss interventions and sustainability of weight-loss efforts.